Characteristic of tree cavities in sal Shorea robusta forest, Nepal. Issue 4 (4th July 2018) - Baral, Rishi; Czeszczewik, Dorota; Walankiewicz, Wiesław; Churski, Marcin; Bhusal, Prabin; Thapa, Tej Bahadur; Mikusiński, Grzegorz
ABSTRACT: Tree cavities are one of the key structures that influence abundance and diversity of cavity-dependent organisms in forests. The natural processes that lead to cavity formation and regulate the abundance of cavities are poorly understood, especially in subtropical regions of Asia. Surveys of tree cavities suitable for breeding birds were conducted in southern Nepal in sal Shorea robusta dominated forest. A cavity was defined as a hole in a tree trunk or a limb with a minimum entrance diameter of 2 cm × 2 cm, interior space, depth at least 2 cm and a solid bottom with a minimum diameter of 5 cm. Within 50 sample plots, we found 104 tree cavities. The mean height of cavity entrances (6.8 m above the ground) varied across tree species from 3.4 m in Dillenia pentagyna to 10.3 m in S . robusta, and was positively correlated with DBH of tree. The entrance exposures were most often to the south (38.2%), and located mainly in trunks (74.0%). Cavity entrances were very different in size, with mean smallest diameter 7.7 cm, the average depth of the cavity was 25.7 cm. Mode of cavity production (excavated or non-excavated) was best predicted by a model including diameter of cavity tree (DBH), cavity height and their interaction. Single check of cavities showed signs of use by birds in 21% of them. Excavated cavities accounted for 27.9% of all cavities, indicating that role of woodpeckers as cavity providers might be of importance for secondary users in sal forest.